Biodegradation of carbamate pesticide (carbofuran) by indigenous bacteria isolated from selected agricultural soil - Mustapha, Mohammed Umar (2020)
Carbofuran is potent endocrine disruptor and compound with neurotoxic effect and continued used bring about their persistence in soil. Carbofuran is highly mobile in soil and soluble in water which causes threat to human health and have long term effect on the environment. Microbial degradation has been recommended as the best approach for the removal of pesticides from the environment since previously used methods were highly expensive. Thus, the aim of the study was to isolate potential carbofuran-degrading bacteria from local soil screen, identify, characterized and checked the degrading ability of the isolated strain. The bacterium was optimized using one factor at a time and response surface methodology. The cells of the bacteria were immobilized using gellan gum as an entrapment matrix. The bacterial growth kinetics was evaluated using different kinetics models. Microcosm study containing four different treatments mixtures were set. The rate of reduction of carbofuran was determined using High-Performance Liquid Chromatography (HPLC). The optimum culture condition of Enterobacter cloacae sp. for carbofuran degradation was at pH 7.0 and the optimum temperature was 35-370C. At gellan gum concentration of 0.8 % (w/v) highest degradation of carbofuran was observed compared with other concentrations used (p≤0.05) however, no significant difference (p≥0.05) was observed with regard to degradation of carbofuran between 0.75 and 0.8 % (w/v). The gellan gum-entrapped cells could also be used repeatedly without loss of biodegradation capacity for up to seven cycles for a total of 200 hours’ cycle. Results obtained using Central Composite Design (CCD) showed that highest carbofuran degradation of 95.40% with optimized carbofuran concentration of 92.50 mg/L, pH of 6.0, temperature 27.50 °C, nitrogen sources of 0.45 g/L and reaction period of 6 days. The predicted values were in agreement with the actual values with coefficient of determination with R2 0.9719. Growth kinetics models reveals that Luong model was best fitted with experimental data with R2 is 0.984 with low values for root mean square error (RMSE). Microcosm study shows that Enterobacter cloacae sp. BRC05 degraded carbofuran efficiently upto 83% in treatment 2, followed by treatment 4 which contained soil amended with bacterial inoculum, carbofuran, and glucose as an additional source of carbon, the percent degradation of carbofuran was 74.8 ± 0.5% of carbofuran. The isolates obtained in this study would provide a novel and effective approach that could be beneficial for the bioremediation of carbofuran insecticide in a polluted environment.